2012
DOI: 10.1097/pec.0b013e3182767ac8
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Engage in Care of Adolescent Emergency Department Patients With Mental Health Problems That Increase Suicide Risk

Abstract: When adolescents are identified in the ED with previously unrecognized mental health problems that increase suicide risk, a brief motivational and barrier-reducing intervention improves linkage to outpatient mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 30 publications
0
80
0
Order By: Relevance
“…In 5 of the 6 trials that demonstrated effective interventions, results were statistically conclusive 24,27,30,36,45 ; in the sixth, the significant effects observed within the first 2 weeks (OR, 2.38 [95% CI, 1.60-3.54]) were not sustained during the 6-month reporting period (OR, 0.86 [95% CI, 0.56-1.32]). 37 Strategies found to improve the rate of outpatient follow-up included structured telephone contact, postdischarge reminders, 24,30 assistance with scheduling an outpatient follow-up appointment during the ED visit, 27,45 and verbal/written instructions or education about the importance of outpatient follow-up. 27 One study involving patients with asthma also found that providing parents with documentation of their child's allergic status improved adherence to scheduled continuity appointments.…”
Section: Tablementioning
confidence: 96%
See 4 more Smart Citations
“…In 5 of the 6 trials that demonstrated effective interventions, results were statistically conclusive 24,27,30,36,45 ; in the sixth, the significant effects observed within the first 2 weeks (OR, 2.38 [95% CI, 1.60-3.54]) were not sustained during the 6-month reporting period (OR, 0.86 [95% CI, 0.56-1.32]). 37 Strategies found to improve the rate of outpatient follow-up included structured telephone contact, postdischarge reminders, 24,30 assistance with scheduling an outpatient follow-up appointment during the ED visit, 27,45 and verbal/written instructions or education about the importance of outpatient follow-up. 27 One study involving patients with asthma also found that providing parents with documentation of their child's allergic status improved adherence to scheduled continuity appointments.…”
Section: Tablementioning
confidence: 96%
“…In most studies, the control group received routine care (n = 13). 26 -29, 31, 33, 34, 36 -38, 40, 43, 45 Three studies included an enhanced usual care: Teach et al 42 (usual care with an asthma educational packet), Asarnow et al 24 (usual care with ED staff trained on linking patients with outpatient care), and Grupp-Phelan et al 30 (usual care with standard referral).…”
Section: Controlmentioning
confidence: 99%
See 3 more Smart Citations